Deviation From The Concept of Levering in Sale and Purchase Transactions Through Criminal Charges of Embezzlement and/or Fraud Based on Goods Invoices - Kongres, Evi; Indradewi, Astrid Athina; Widjaja, Johanes Dipa (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2026)
Criminal allegations of embezzlement in sale-and-purchase transactions, most frequently initiated by sellers, constitute tangible evidence of a deviation from the legal concept of levering (delivery). Accordingly, the legal issue addressed in this research concerns the deviation from the concept of levering in relation to the principle of freedom of contract and the criminalization of embezzlement and/or fraud arising from non-performance in sale and purchase transactions evidenced by goods invoices. This issue arises from the seller’s assumption that a goods invoice does not constitute a binding agreement, which is based on the belief that ownership of the goods remains with the seller despite delivery to the buyer. This research seeks to clarify the legal concept of levering in sale and purchase transactions and its relationship with the principle of freedom of contract, particularly in the context of goods invoices, with the aim of preventing the transformation of civil sale and purchase agreements into criminal cases, through legislative approaches, case studies, and conceptual analysis. In the cases analyzed, it appears that courts generally fail to apply the two principal benchmarks established in jurisprudence, namely (i) the existence of a legally valid agreement, and (ii) the absence of bad faith. As a result, judicial decisions continue to blur the boundary between civil liability and criminal liability. The novelty of this research lies in emphasizing that the concept of levering grounded in the principle of freedom of contract, cannot be applied within the framework of the criminal offense of embezzlement.